Strength enhancement of structural steel EK-181 based on the multilevel approach of physical mesomechanics; Physical Mesomechanics; Vol. 11, iss. 1-2, Jan.-Apr - Panin A. V.; Leontyeva-Smirnova M. V.; Chernov V. M.; Panin V. E. Viktor Evgenyevich; Pochivalov Yu. I.; Melnikova E. A. (2008, 2008)
Based on the multilevel approach of physical mesomechanics, we have developed a method for hardening of structural steel EK-181 (in the Russian designation) through the formation of a fragmented band structure in its surface layers. Novel deformation mechanisms in steel EK-181 at the mesoscale level are disclosed. They agree well with the theory of a chessboard-like stress distribution at the "hardened surface layer - substrate" interface. We propose a method of stabilizing the hardened surface layer for the steel working at temperatures up to 700 °C